Usher Syndrome with Posterior Subcapsular Cataract - Bramantya Surya Pratama; Nadia Artha Dewi (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction: Usher Syndrome (USH) is an autosomal recessive disorder characterized by congenital sensorineural deafness and progressive loss of vision due to retinitis pigmentosa. The aim of this report is to report rare cases of USH by perform diagnostic steps based on clinical examination and family history with expectations that if a similar case is found, an earlier diagnosis and rehabilitation can be done. Methods: Diagnosis is based on history, ophthalmology examination and ear, nose, and ear (ENT) examination. Results: A 23-year-old man came to the Ophthalmology Outpatient Department with complaints of bilateral blurred vision especially at night and visual field constriction starting 12 years ago. The patient experienced gradual vision deterioration followed by appearance of white spot in his left eye. Patient is deaf and mute since birth. Three family members of the paternal line exhibit the same symptoms. The best corrected visual acuity was right eye 6/15 and left eye hand movement. Bilateral cataract was found during eye examination. Posterior segment examination revealed peripheral bone spiculae appearance and waxy pallor optic disc in both eyes. Loss of neurosensory layer, worse in the left eye, was discovered through Optical Coherence Tomography (OCT). Humphrey perimetry of the right eye indicated tunnel vision. Examination by otorhinolaryngologist revealed a sensorineural hearing loss. In this patient, there is no management for the disorders due to the poor prognosis of visual acuity. What can be done to improve the patient's quality of life is supportive therapy. It is important to screen and educate families suffering from the same disorder for early diagnosis & rehabilitation. Conclusion: Clinical examination and family history confirm the diagnosis of USH. Early diagnosis and early rehabilitation are essential to improve patient's quality of life. In this case, no management was carried out for the cataracts because the visual acuity of both eyes did not match the cloudiness of the lens so there are possibility the visual acuity could not improve. Rehabilitations that can be done for the patients are visual and social rehabilitation to improve quality of life.